Embracing New Realities: Professional Growth for New Principals and Mentors - Donna Augustine-Shaw; Jia Liang (Educational Considerations, 2016)
This paper highlights one state model providing mentoring and induction for new school leaders in the U.S.A. The importance of mentoring and induction as a continuation of leadership preparation is highlighted in program components and participant perceptions in The Kansas Educational Leadership Institute’s (KELI) mentoring and induction program and professional learning seminars. Experienced and trained mentors provide critical support for new principals serving schools and communities in their first year of practice. A program description, initial operational processes, program requirements, and mentor training are shared along with information about KELI’s second year program, evaluation results, and next steps.
Keywords: principal; New leaders; The Kansas Educational Leadership Institute (KELI); experience; Mentoring; induction Program; participation; Moving Forward; Evaluation and Success; Implications for Practice